United Nations Disarmament Yearbook 2019: Part II - Bureau des affaires du désarmement des Nations Unies (United Nations, 2020)
This publication summarizes developments and trends in 2019 on key issues of multilateral consideration at the international and regional levels. It reviews the activity of the General Assembly, the Conference on Disarmament and the Disarmament Commission. It contains a timeline that highlights events in multilateral disarmament in 2019 and comprises a foreword written by the High Representative for Disarmament Affairs.